Leveraging e-WOM and green service quality to boost revisit intentions green hotels - Khoerunisa, Mutia; Astuti, Miguna; Mardiatmi, Bernadin Dwi (Goodwood Publishing, 2025)
Purpose: This study examines the effects of Green Service Quality (GSQ) and electronic word of mouth (e-wom) on tourist satisfaction and revisit intention in eco-friendly hotels, with tourist satisfaction as a mediating variable. Methodology/approach: Using a quantitative approach, data were collected through a structured questionnaire distributed to individuals who had stayed at green hotels in Jakarta. Purposive sampling was applied, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results/findings: The results show that both GSQ and e-WOM significantly influence Tourist Satisfaction and Revisit Intention. Tourist Satisfaction also mediates the relationship between GSQ and e-WOM with Revisit Intention. Among all variables, Tourist Satisfaction is the strongest predictor of revisit intention. Conclusions: These findings highlight that high-quality green services and positive e-WOM enhance guest satisfaction and loyalty. Satisfied guests tend to return and recommend the hotel, strengthening its reputation and supporting long-term sustainability. Limitations: However, the study has limitations, including reliance on self-reported data and a geographically limited sample. Other factors such as pricing or hotel branding were not considered. Contribution: This research contributes to the green hospitality literature by confirming the mediating role of satisfaction and offering managerial insights on how sustainable practices and digital engagement can drive customer loyalty.